Screaming mothers in Malayalam cinema: motherhood as a genre-defying identity in Malayalam cinema - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2022)
The image of the mother is perhaps one of the most recurring identities in cinema. Even if we do not count those films where a mother is the main protagonist, there are countless films in which the presence of mothers cannot be overlooked. This familiarity with which mothers get over-identified in films makes their representations stereotypical and strictly adhering to the cultural and political mores of the society. Traditionally considered as the most powerful version of femininity, motherhood is often overtly romanticized as the symbolization of ideal female expression. The visual language of Indian cinema has been contributing greatly to the construction of the ideal mother image for a long time, and it chiefly consists of a semiotics full of signifiers that glorify the emotional vulnerability, sacrifice, courage, and suffering associated with motherhood. The performative aspects of motherhood can easily be observed as important in the context of the melodramatic and sentimentalist tradition of Bollywood cinema.
Keywords: motherhood; Indian cinema